Study of the Conceptual Model of Intelligence Coordination in Indonesia Using SSM - Oktora Aditia; Amy Y. S. Rahayu; Roy Valiant Salomo (Journal La Sociale, 2026)
Coordination of state intelligence is one source of problems which also widens the spectrum of national threats in Indonesia. Errors in how to act in reducing threats, data errors, and the inability of the Intelligence Community (IC) to collectively read symptoms, are forms of intelligence failure as an early warning and early detection country. The threat dynamics also continue to develop, now they are no longer traditional (military) but even non-military hybrid, requiring the IC to improve the coordination system and share information with each other. The two main causes and interplay between ambiguous policies and high levels of institutional ego among IC members, lead to competition because each IC member reports directly so that the President assesses them as more active and productive (the single user of intelligence). Such conditions make it difficult for the President to assess analysis bias, data accuracy and the effectiveness of suggestions from the amount of information received. This study presents an illustration of the conceptual model of the state intelligence coordination system in Indonesia, using a qualitative approach with the instrument of the Soft Systems Methodology (SSM) to overcome problems in complex coordination systems (messy situations) and involving many actors with goals that are not always the same. PQR analysis, CATWOE and 3E are used in an action-oriented inquiry process to change, improve, and perfect the problematic situation of the selected system. This study produces a conceptual model that can be used as material for discussion and debate in determining purposeful activity, especially on four problems; negative stigma about sharing information, reporting dualism, membership ambiguity, and low compliance. The chosen fourth root definitions lead to transformation in the form of policy changes that emphasize the importance of sharing information, clarity of the reporting system, membership structure, and the obligation to carry out the IC coordinator's recommendations.